Diosgenin: an important natural pharmaceutical active ingredient - HUANG,Nannan (2022)
Abstract Diosgenin is a steroidal saponin isolated from dioscorea opposita, which has been proven to have anti-cancer, anti-inflammatory, anti-thrombotic and immune system modulating effects in a large number of pharmacological tests. Diosgenin is also one of the important raw materials for the synthesis of steroidal drugs, and structural modification of diosgenin to obtain diosgenin derivatives can not only improve the solubility and dissolution, but also enhance their pharmacological effects. This paper reviews the synthetic reactions, pharmacological effects of diosgenin and its derivatives, aiming to provide detailed information for the further development and application of diosgenin, which is important to improve the utilization value of diosgenin.